2019
DOI: 10.5811/cpcem.2019.9.43674
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Hemorrhagic Shock: Morel-Lavallée Lesion

Abstract: Hemorrhage is a major cause of death among trauma patients. Controlling the bleeding is essential but can be difficult when the source of bleeding remains unidentified. We present a 67-year-old healthy male with a hypovolemic shock after a suicide attempt by jumping from a height. Apart from a bilateral pneumothorax with multiple rib fractures, a femur fracture and spine fractures, computer tomography (CT) revealed a closed, degloving injury of the back, also known as a Morel-Lavallée lesion. Hemodynamic insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…In one report of a posterior trunk MLL, supine positioning and compression using the patient’s body weight successfully tamponaded the lesion. 14 The risk of pressure ulceration secondary to continuous bedrest should be considered with this approach. Additionally, observation carries a risk of vascular compromise to overlying tissue if there is pressure-related ischemia from the accumulated fluid.…”
Section: Discussionmentioning
confidence: 99%
“…In one report of a posterior trunk MLL, supine positioning and compression using the patient’s body weight successfully tamponaded the lesion. 14 The risk of pressure ulceration secondary to continuous bedrest should be considered with this approach. Additionally, observation carries a risk of vascular compromise to overlying tissue if there is pressure-related ischemia from the accumulated fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Unless a delayed diagnosis may cause devastating consequences like a hemorrhagic shock which is a rare complication and only four cases have been described in the literature. Classen et al [ 5 ] reported a case of MLS situated in the lumbar region treated with conservative treatment based on compression using the patient’s own body weight. Hefny et al [ 6 ] reported a case of MLS in the flunk treated by percutaneous suction drainage.…”
Section: Discussionmentioning
confidence: 99%
“…• In the absence of a specific guideline/protocol for the management of soft tissue compartment bleeding, treatment should be individualized based on the hemodynamic status of the patient. Hefny et al [6] Extensive hematoma between the subcutaneous fat and the paraspinal muscles in the back Percutaneous suction drain Discharged Yumoto et al [7] Large hematoma in the lower back with lumbar vertebrae fractures with active contrast extravasation at multiple sites located close to the bilateral lumbar and internal iliac arteries Gel foam embolization Discharged Mao et al [8] Left flank to thigh NOM but later required open drainage for infected collection Discharged Claassen et al [9] Lower lumbar region in the back NOM Discharged Daghmouri et al [10] Lumbar region extending to hips and both legs Surgical drainage Discharged NOM, nonoperative management.…”
Section: Learning Pointsmentioning
confidence: 99%